1985
DOI: 10.1007/bf02266940
|View full text |Cite
|
Sign up to set email alerts
|

Induction of fruit set and development in pea ovary explants by gibberellic acid

Abstract: The response of unpollinated ovary explants of Pisum sativum L. cv. Alaska No. 7 to several plant growth regulators and nutrients has been studied. Explants consisted of a segment of stem and an emasculated flower with or without the adjacent leaf. They were made on the day equivalent to anthesis and were cultured in a liquid medium. Growth regulators were applied either in the solution or directly to the ovaries. Gibberellic acid (GA 3) in the presence of sucrose, but not indole-3-acetic acid or N6-(A2-isopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The percentage of fruit production was increased in all treated plants over control. This finding is in agreement with reports On GA3-induced fruit set in plants other than cucurbits (Agusti et al 1982, Holloway-Patrica et al 1982, Garcia-Martinez and Carbonell 1985 and on the effect of ethrel on growth, flowering and fruit formation of three cucurbits (Sadhu and Das 1978).…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of fruit production was increased in all treated plants over control. This finding is in agreement with reports On GA3-induced fruit set in plants other than cucurbits (Agusti et al 1982, Holloway-Patrica et al 1982, Garcia-Martinez and Carbonell 1985 and on the effect of ethrel on growth, flowering and fruit formation of three cucurbits (Sadhu and Das 1978).…”
Section: Discussionsupporting
confidence: 93%
“…Pea (Pisum sativum) has been used to study the effects of gibberellic acid on fruit set and development. Garcia-Martinez & Carbonell (1980, 1985 found that unpollinated pea ovaries treated with gibberellic acid/(GA3) developed into mature fruits, while unpollinated untreated ovaries senesced. The cells of the pea carpel walls enlarge and differentiate as the fruit matures following pollination.…”
Section: Fruit Development and Structurementioning
confidence: 99%